Validitas Instrumen Aktivitas Belajar Siswa dalam Pembelajaran Fisika - Zavira, Noveliani; Sari, Silvi Yulia (Lembaga Yasin AlSys, 2023)
The learning process certainly includes learning activities. A person who engages in learning activities thinks about ideas while taking action or engaging in physical activity. The importance of learning activities in fostering learning discipline so that student learning outcomes can improve. Based on observations, student learning activities in learning physics in class are still low. This is due to the lack of development of learning activity instruments in physics learning. This study aims to develop instruments of student learning activities in physics learning that are valid for use in the implementation of research. The method used in this study is a literature study with data analysis techniques using AikenV assessors. The physics learning activity instrument that will be developed is oriented to student activities. The eight exercises that can compose the tool for assessing student learning activities include visual activities, oral activities, listening activities, writing activities, drawing activities, motor activities, mental activities, and emotional activities. Each of the indicators within these eight activity instruments will be subjected to tests to determine their validity.The findings of this study show that the instrument falls into the medium category, with a validity score of 0.778, according to the results of the AikenV validity test. Thus, it is concluded that the instrument of student learning activities in physics learning is feasible to implement research.